2024
DOI: 10.2196/50189
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Clustering Unhealthy Lifestyles Among Survivors of COVID-19: Latent Class Analysis

Lan T H Le,
Thi Ngoc Anh Hoang,
Tan T Nguyen
et al.

Abstract: Background The COVID-19 pandemic has underscored the significance of adopting healthy lifestyles to mitigate the risk of severe outcomes and long-term consequences. Objective This study focuses on assessing the prevalence and clustering of 5 unhealthy lifestyle behaviors among Vietnamese adults after recovering from COVID-19, with a specific emphasis on sex differences. Methods The cross-sectional data of 58… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…32 Males are more susceptible to the influence of unhealthy lifestyles. 33 The association between dietary quality and accelerated aging is particularly pronounced among individuals with unhealthy lifestyles, including alcohol consumption and prolonged sedentary behavior. Previous research has demonstrated the association between unhealthy lifestyles and aging.…”
Section: Discussionmentioning
confidence: 99%
“…32 Males are more susceptible to the influence of unhealthy lifestyles. 33 The association between dietary quality and accelerated aging is particularly pronounced among individuals with unhealthy lifestyles, including alcohol consumption and prolonged sedentary behavior. Previous research has demonstrated the association between unhealthy lifestyles and aging.…”
Section: Discussionmentioning
confidence: 99%